Empty Delta Sign on Unenhanced Postmortem Computed Tomography Scan in Cerebral Venous Thrombosis. (December 2018) - Garland, Jack; Kesha, Kilak; Vertes, Dianne; Modahl, Lucy; Milne, David; Ruder, Thomas; Stables, Simon; Tse, Rexson
Abstract : Abstract: Cerebral venous thrombosis is a rare condition which constitutes 0.5% to 2% of all types of stroke and carries a mortality of up to 20% to 50%. It leads to cerebral edema, infarction, hemorrhage and venous hypertension. Clinically the diagnosis is confirmed using enhanced computed tomography (CT) angiography which demonstrates an empty delta sign in cerebral veins, particularly in the superior sagittal sinus. However, postmortem CT (PMCT) findings on cerebral venous thrombosis have not been documented in the literature. We present a case report of a 69-year-old man who on unenhanced PMCT scan showed an empty delta sign in the cerebral veins. The empty delta sign was able to be demonstrated in unenhanced PMCT which can be explained by hyper attenuation of the dural veins at postmortem forming an internal contrast highlighting the thrombus.